16 bits x 16 bits booth multiplier using VHDL - Muhammad Syafiq, Norashid (2008)
Nowadays, digital device is very important to all the people in this world. The high speed operation and less space and energy required had made the digital devices more preferred. This project is to design digital system which performed fixed point Booth Multiplier where the design system would be developed using hardware description language (HDL), in this case, VHDL (VHSIC Hardware Description Language), VHSIC stands for Very High Speed Integrated Circuit. The Software used would be Xilinx ISE 10.1 which is the software used to designed digital system for Xilinx manufactured FPGA board. The algorithm to design the system is Booth Multiplier Algorithm. The designed digital system will receive two 16 bits input and processes it to create a 32 bits output with the value of the multiplied inputs data value. Finally, it is proven that the system created can calculate and yield a fixed point multiplied output of the input value.